2017
DOI: 10.21069/app.2017.10366
|View full text |Cite
|
Sign up to set email alerts
|

Neurodesenvolvimento em Crianças Nascidas Pré-Termo de Muito Baixo Peso: Fatores de Risco Ambientais e Biológicos

Abstract: Introdução: Pretendeu-se avaliar o neurodesenvolvimento em recém-nascidos pré-termo de muito baixo peso aos 24-30 meses de idade e correlacioná-lo com fatores de risco biológicos e ambientais. Métodos: Estudo observacional, retrospetivo de uma coorte de crianças nascidas entre janeiro de 2005 e dezembro de 2013, com idade gestacional inferior a 32 semanas e/ou peso de nascimento inferior a 1500 g numa maternidade de apoio perinatal diferenciado. Avaliou-se o neurodesenvolvimento aos 24-30 meses através da sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…As it is described in the literature, lower status is a risk factor for NDI. [3,7,35,43] In our study, the bivariate analysis showed that a higher level of maternal education was a protective factor for NDI, however this was not demonstrated in the multivariate analysis. In a systematic review, unlike factors related to infant characteristics, the in uence of parental education appeared to persist into middle childhood.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…As it is described in the literature, lower status is a risk factor for NDI. [3,7,35,43] In our study, the bivariate analysis showed that a higher level of maternal education was a protective factor for NDI, however this was not demonstrated in the multivariate analysis. In a systematic review, unlike factors related to infant characteristics, the in uence of parental education appeared to persist into middle childhood.…”
Section: Discussioncontrasting
confidence: 77%
“…6%). [28,35] In our study, the incidence of CP was lower (4.8% in GA ≤ 27w and 3% at 28-31w) than what is reported in surveillance of cerebral palsy in Europe: 14% at ≤ 27w of GA, 6% at 28-31w and < 1% at 32-36w. [6, 28] Comparison with other studies in relation to the presence of NDI must be made with caution, since the methodology, the scale applied and the population studied differ in the various published studies.…”
mentioning
confidence: 42%
See 2 more Smart Citations